Prognosis and treatment of primary adenocarcinoma and adenosquamous cell carcinoma of the uterine cervix - (:unkn) unknown (I R O G CANADA, INC, 2001)
Purpose: To evaluate a cohort of women with primary invasive carcinomas of the uterine cervix, and to compare the biological characteristics and behavior of a cohort of adenosquamous carcinomas with a cohort of adenocarcinomas and squamous cell carcinomas. Methods: One hundred and fourteen cases of primary invasive cervical carcinoma presenting between 1 January 1987 and 31 December 1997 were studied. Sixteen (14%) women with adenosquamous cell carcinomas and eight (7%) adenocarcinomas were compared with 90 (79%) women with squamous cell carcinomas. Patients with Stage Ib and IIa were treated by radical hysterectomy and pelvic lymph node dissection. All patients with stage IIb and over were treated by radiation. Patients with bulky, large, barrel-shaped lesions were selected for treatment by a combination of radiation and extrapelvic hysterectomy. Results: The corrected survival rate for stage Ib patients with adenosquamous cell carcinoma was only 27.2%, compared with a 92.2% corrected survival rate for squamous cell, and a 100% corrected survival rate for adenocarcinoma. Conclusion: There is a higher proportion of adenosquamous cell and adenocarcinoma of the cervix than generally appreciated. The epidemiological risk factors associated with adenosquamous carcinomas of the cervix are more similar to those of squamous cell carcinomas than of adenocarcinomas. The survival difference between two groups is explained by effects of clinical stage, nodal spread, and vascular space involvement.
Keywords: adenosquamous cell carcinoma; adenocarcinoma; squamous cell carcinoma; survival; uterine cervix; YOUNG-WOMEN; CANCER; HYSTERECTOMY